The effectiveness of social media in spreading health campaigns / Siti Nur Rabiatuladawiyah Juharlizam and Aini Faezah Ramlan - Juharlizam, Siti Nur Rabiatuladawiyah; Ramlan, Aini Faezah (Faculty of Communication & Media Studies, 2022)
Mass media is a medium of information transmission that is so important to the world. The emergence and development of social media as a new communication tool has provided a lot of convenience to its users. Health campaigns are created to raise awareness about health to the community and aim to share knowledge regarding health issues. The widespread use of social media has made social media a useful medium for spreading information and promoting health care. The criteria that needed to find journals is a factors of social media as a spreading awareness about health campaign and a total of 11 journals were carefully selected and met the criteria.